Immune checkpoint blockade for non–small cell lung cancer: What is the role in the special populations?. (January 2020) - Califano, R.; Gomes, F.; Ackermann, C.J.; Rafee, S.; Tsakonas, G.; Ekman, S.
Abstract: In recent years, non–small cell lung cancer (NSCLC) entered in a new era of anticancer treatments with the success of checkpoint inhibitors (CPIs). These are now part of daily practice from locally advanced to metastatic NSCLC. However, the registration phase III trials are highly selective and not fully representative of the patients seen in real-world clinical practice. This is particularly obvious for older and frail patients, which represent the majority of NSCLC cases worldwide. The median age of the patients enrolled in clinical trials is 10 years younger than what is seen in clinic and patients with performance status (PS) ≥2 were excluded from registration studies. No strong conclusions can be drawn from the available trials where older and frail patients have been excluded. The majority of data on efficacy according to age are derived from underpowered subgroup analysis and there are no age-specific safety data published. Current data suggest that older patients may derive a similar benefit with no increased toxicity when compared with younger patients. However, the recent development of immunotherapychemotherapy combinations and the potential higher incidence of toxicity, raise additional concerns for these populations where adequate patient selection is paramount. CPI is not recommended for patients with PS 3–4 and should be considered with caution for those with PS 2. The evidence for patients with pre-existing autoimmune disease (AID), organ transplant or chronic viral infections (such us viral hepatitis B and C or human immunodeficiency virus) is less clear and low level. Although CPI are potentially safe in selected patients with AID with minimal activity and well-controlled chronic viral infections, patients with solid organ transplant face a significant risk of graft loss and death. Therefore, a decision to treat these groups of patients should always be discussed at a multidisciplinary level. Highlights: Checkpoint inhibitors revolutionised the treatment pathway for advanced non–small cell lung cancer (NSCLC). There is increasing evidence supporting their use in older cancer patients. Data on patients with a performance status score of 2 raise concerns on its efficacy within NSCLC. Data is scarce for patients with autoimmune disease, organ transplant, or chronic viral infections.